Remembering the medieval present
1 online resource.
Keywords: This volume of essays focuses on how individuals living in the late tenth through fifteenth centuries engaged with the authorizing culture of the Anglo-Saxons. Drawing from a reservoir of undertreated early English documents and texts, each contributor shows how individual poets, ecclesiasts, legists, and institutions claimed Anglo-Saxon predecessors for rhetorical purposes in response to social, cultural, and linguistic change. Contributors trouble simple definitions of identity and period, exploring how medieval authors looked to earlier periods of history to define social identities and make claims for their present moment based on the political fiction of an imagined community of a single, distinct nation unified in identity by descent and religion. Contributors are Cynthia Turner Camp, Irina Dumitrescu, Jay Paul Gates, Erin Michelle Goeres, Mary Kate Hurley, Maren Clegg Hyer, Nicole Marafioti, Brian O’Camb, Kathleen Smith, Carla María Thomas, Larissa Tracy, and Eric Weiskott.